1985
DOI: 10.1073/pnas.82.13.4558
|View full text |Cite
|
Sign up to set email alerts
|

Activity regulates the levels of acetylcholine receptor alpha-subunit mRNA in cultured chicken myotubes.

Abstract: In vitro blocking the spontaneous activity of primary cultures of chicken embryo myotubes with tetrodotoxin increases~2-fold their content in surface acetylcholine receptor. To investigate this effect at the level of gene expression, chicken genomic DNA sequences coding for the acetylcholine receptor a subunit were isolated and characterized. They were shown to belong to a single-copy, polymorphic gene with at least two alleles in the chicken strain utilized. Probes derived from these genomic clones were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
65
1
1

Year Published

1987
1987
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(74 citation statements)
references
References 44 publications
7
65
1
1
Order By: Relevance
“…Finally, muscle electrical activity represses the expression of the AChR (15), and this effect can be studied in vitro, e.g., by using tetrodotoxin to block the spontaneous electrical activity of cultured myotubes (39). Such changes in AChR expression have been correlated with variations of the mRNA levels for its a-subunit (24); similar results have been obtained after muscle denervation in vivo (24,28).…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Finally, muscle electrical activity represses the expression of the AChR (15), and this effect can be studied in vitro, e.g., by using tetrodotoxin to block the spontaneous electrical activity of cultured myotubes (39). Such changes in AChR expression have been correlated with variations of the mRNA levels for its a-subunit (24); similar results have been obtained after muscle denervation in vivo (24,28).…”
supporting
confidence: 55%
“…Characterization of 5' end of chicken AChR a-subunit gene. Several laboratories, including ours, had previously isolated and identified genomic clones encoding the chicken AChR a-subunit (2,24) on the basis of its high degree of sequence conservation with its counterparts in other species (5,12,33,34). To map the first exon, the length of mRNA between the sequence corresponding to the exon named P2 in the human gene (24,33) and the mRNA capsite was assessed by primer extension with reverse transcriptase, using poly(A)+ RNA * Corresponding author.…”
mentioning
confidence: 99%
“…In contrast, when denervated muscle is electrically stimulated, intracellular calcium concentrations are elevated (4), and receptor expression is suppressed (6 -8). Similarly, receptor expression is suppressed in TTX-treated myotubes when they are exposed to calcium-elevating drugs (2,3,9,10). Although muscle depolarization and increases in intracellular calcium can initiate the process of nAChR suppression in extrajunctional nuclei, the signal transduction pathways involved in these processes remain controversial.…”
Section: Nicotinic Acetylcholine Receptors (Nachrs)mentioning
confidence: 99%
“…Recent analysis of the mechanisms underlying the increased receptor synthesis rate has revealed that denervation also results in a remarkable increase in mRNAs coding for the individual receptor subunits [4][5][6][7][8][9][10][11]. The increased message concentrations in turn are at least in part caused by enhanced transcription rates of receptor genes [1,12]; in the chicken a denervation signal reaches the genome and activates the t~-, 6-, and 7-subunit genes within 12 h after nerve section [12].…”
Section: Introduction Denervation Of Adult Skeletal Muscle Induces Exmentioning
confidence: 99%
“…For example, it is not known if denervation results in the appearance of an activating factor or in the loss of an inhibitor. Treatment of primary muscle cells with the sodium channel blocker tetrodotoxin results in an increase of AChR protein and ct-subunit mRNA, and has been employed to analyze the effects of membrane electrical activity on receptor gene expression [5,11,13]. Using this in vitro model of denervation, Duclert et al [14] have shown that inhibition of protein synthesis blocks the tetrodotoxin-induced rise in a-subunit message level We have investigated the metabolism of the AChR subunit messages in denervated chick skeletal muscle.…”
Section: Introduction Denervation Of Adult Skeletal Muscle Induces Exmentioning
confidence: 99%